The influence of relative age on the selection of players for elite events in junior football - Matušica, M.; Perácek, P. (Journal of Physical Education and Sport, 2023)
The aim of this research is to expand knowledge about the influence of relative age on the selection of players for elite junior football events (UEFA European Championship, Confederation of African Football, ASEAN Football Federation Championships, UEFA Youth League). Among elite clubs, we have included national teams for the UEFA European Championship U19, U17 2022, men and women, UEFA Youth League in the years 2019/2020, 2021/2022, 2022/2023, CAF U20 2021, AFF U19 2022. In individual teams, we determined the months in which the players were born and then assigned them to the respective quarter. In total, we tracked 4048 players from 158 teams in categories from U17 to U20 at national and club level. To obtain the necessary data, we used the basic mathematical-statistical method Chi-square (goodness-of-fit test). Among men, we found the smallest differences between the first and last quarter, in the number of players born in each quarter of the calendar year in CAF 2021. This means that the influence of relative age on the inclusion of a player on the roster in this age category disappears. We found the biggest quarterly differences in all years of UEFA Youth League 2019/2020, 2021/2022, 2022/2023. We also compared two women's championships, namely EURO WU17 and WU19. In this case, there was a difference in the number of female players born in one month,especially in the first and second quarters of the calendar year. Based on the results, we recommend that coaches utilise somatic acceleration (biological age) as a selection criterion during the initial screening of talented players along with other factors when assessing the appropriateness of including a player on the team roster.